Assessment of liver viscoelasticity by using shear waves induced by ultrasound radiation force - Chen, Shigao; Sanchez, William; Callstrom, Matthew R; Gorman, Brian; Lewis, Jason T; Sanderson, Schuyler O; Greenleaf, James F; Xie, Hua; Shi, Yan; Pashley, Michael; Shamdasani, Vijay; Lachman, Michael; et al. (Radiology, 2013)
To investigate the value of viscosity measured with ultrasonographic (US) elastography in liver fibrosis staging and to determine whether the use of a viscoelastic model to estimate liver elasticity can improve its accuracy in fibrosis staging. The study, which was performed from February 2010 to March 2011, was compliant with HIPAA and approved by the institutional review board. Written informed consent was obtained from each subject. Ten healthy volunteers (eight women and two men aged 27-55 years) and 35 patients with liver disease (17 women and 18 men aged 19-74 years) were studied by using US elasticity measurements of the liver (within 6 months of liver biopsy). US data were analyzed with the shear wave dispersion ultrasound vibrometry (SDUV) method, in which elasticity and viscosity are measured by evaluating dispersion of shear wave propagation speed, as well as with the time-to-peak (TTP) method, where tissue viscosity was neglected and only elasticity was estimated from the effective shear wave speed. The hepatic fibrosis stage was assessed histologically by using the METAVIR scoring system. The correlation of elasticity and viscosity was assessed with the Pearson correlation coefficient. The performances of SDUV and TTP were evaluated with receiver operating characteristic (ROC) curve analysis. The authors found significant correlations between elasticity and viscosity measured with SDUV (r = 0.80) and elasticity measured with SDUV and TTP (r = 0.94). The area under the ROC curve for differentiating between grade F0-F1 fibrosis and grade F2-F4 fibrosis was 0.98 for elasticity measured with SDUV, 0.86 for viscosity measured with SDUV, and 0.95 for elasticity measured with TTP. The results suggest that elasticity and viscosity measured between 95 Hz and 380 Hz by using SDUV are correlated and that elasticity measurements from SDUV and TTP showed substantially similar performance in liver fibrosis staging, although elasticity calculated from SDUV provided a better area under the ROC curve.